Geophysical assessment of illegally buried toxic waste for a legal enquiry: A case study in Northern Ireland (UK). Issue 4 (2nd October 2018) - Ruffell, Alastair; Pringle, Jamie K.; Graham, Conor; Langton, Mike; Jones, Glenda M.
Abstract: Buried illegal waste and uncontrolled legal waste dumps are a major problem throughout the world, both in developing and more economically developed countries. Criminal investigations can effectively use geoscience techniques to better understand how to locate and characterize such waste. When a case is brought to the courts, the volume, areal extent of the likely waste and land ownership needs to be estimated. This article presents a brief overview of how the investigative process currently occurs and evidences the estimation of waste volume and land owner areas by a case study. The case study illustrates how a combination of geodetic topographic and near-surface geophysics surveys were used to both determine the amount of illegal waste present on a site and assess whose land (in this case, above or below High Tide Mark) the material had been buried on.